Update breast cancer 2020 part 5 - moving therapies from advanced to early breast cancer patients = Update Mammakarzinom 2020 Teil 5 – Einführung von Substanzen aus der metastasierten Therapiesituation in die frühe Therapiesituation - Lux, Michael Patrick; Schneeweiss, Andreas; Hartkopf, Andreas; Müller, Volkmar; Janni, Wolfgang; Belleville, Erik; Stickeler, Elmar; Thill, Marc; Fasching, Peter Andreas; Kolberg, Hans-Christian; Untch, Michael; Harbeck, Nadia; et al. (Geburtshilfe und Frauenheilkunde, 2021)
In recent years, significant progress has been made in new therapeutic approaches to breast cancer, particularly in patients with HER2-positive and HER2-negative/hormone receptor-positive (HR+) breast cancer. In the case of HER2-positive tumours, these approaches have included, in particular, treatment with pertuzumab, T-DM1, neratinib and, soon, also tucatinib and trastuzumab deruxtecan (neither of which has yet been authorised in Europe). In patients with HER2−/HR+ breast cancer, CDK4/6 inhibitors and the PIK3CA inhibitor alpelisib are of particular importance. Further novel therapies, such as Akt kinase inhibitors and oral SERDs (selective estrogen receptor down regulators), are already being investigated in ongoing clinical trials. These therapeutic agents are not only being introduced into curative, (neo-)adjuvant therapeutic settings for HER2-positive tumours; a first favourable study on abemaciclib as an adjuvant therapy has now also been published. In patients with triple-negative breast cancer, after many years of negative study results with the Trop-2 antibody drug conjugate (ADC) sacituzumab govitecan, a randomised study has been published that may represent a significant therapeutic advance. This review describes the latest developments in breast cancer subsequent to the ESMO Congress 2020.
Gesehen am 14.07.2021